2004
DOI: 10.1097/01.sla.0000137141.55267.47
|View full text |Cite
|
Sign up to set email alerts
|

One Thousand Minimally Invasive Valve Operations

Abstract: Minimally invasive valve surgery can be performed at very low levels of morbidity and mortality, with results equal to or better than conventional techniques. All forms of valve repair and replacement operations can be performed. Long-term survival and freedom from reoperation are excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
212
2
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(231 citation statements)
references
References 15 publications
9
212
2
8
Order By: Relevance
“…The commonly raised disadvantages of minimally invasive approaches include longer perfusion and cross-clamp times and a greater risk for stroke (9). However, several studies have shown that the risk of stroke is in fact not greater with minimally invasive approaches (20,22,23). In addition, we have demonstrated that myocardial ischemic times, cardiopulmonary bypass times and the rate of complications can be lower or similar with minimally invasive approaches (13).…”
Section: Pros and Cons Of Surgical Approachesmentioning
confidence: 73%
See 1 more Smart Citation
“…The commonly raised disadvantages of minimally invasive approaches include longer perfusion and cross-clamp times and a greater risk for stroke (9). However, several studies have shown that the risk of stroke is in fact not greater with minimally invasive approaches (20,22,23). In addition, we have demonstrated that myocardial ischemic times, cardiopulmonary bypass times and the rate of complications can be lower or similar with minimally invasive approaches (13).…”
Section: Pros and Cons Of Surgical Approachesmentioning
confidence: 73%
“…Minimally invasive and conventional approaches are equally safe, with no significant differences in mortality, safety and efficacy, and with outcomes highly dependent on surgeon expertise (10,20,21). Minimally invasive surgical techniques were initially introduced in the mid-1990s with a goal of minimizing surgical trauma while preserving the safety and quality achieved by conventional surgery.…”
Section: Pros and Cons Of Surgical Approachesmentioning
confidence: 99%
“…[5][6][7][8][9]15) Although the RPA has been used in the past, partial sternotomy with no specialized equipment has recently become the predominant approach. A few studies have reported transition from the RPA to partial sternotomy in minimally invasive aortic valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported transition from the RPA to partial sternotomy in minimally invasive aortic valve surgery. 5,6) The reasons for this transition may be that partial sternotomy can easily convert to full median sternotomy and that the RPA is associated with the potential to sacrifice the right Data are expressed as mean ± SD or number of patients internal thoracic artery. Moreover, the RPA may result in lung hernia or flail chest, which may require surgical treatment and contribute to poor wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Expedited extubation may result from enhanced preservation of mechanical chest wall functionality, or alternatively from different management protocols. Less invasive mitral valve surgery reproducibly shortens ICU and hospital length of stay compared to that through median sternotomy (6,19,20,22,27,28). This benefit may be more pronounced in sternal-sparing mitral valve surgery.…”
mentioning
confidence: 90%